Kesadaran Santri dalam Pengelolaan Sampah dengan Metode Reuse, Reduce dan Recycle - Windi; Ahmad Aguswin; Akhmad Akromusyuhada (SAFE-Network, 2023)
The higher and the increasing amount of waste in Indonesia, the proper waste management is needed. The new paradigm of waste management as mandated by RI Law no. 18 of 2008 concerning waste management, a real effort is needed to make it happen. Al-Muhajirin Islamic Boarding School is one of the Islamic boarding schools in Bekasi Regency, West Java. The students at the Islamic boarding school still do not have knowledge about waste management based on reuse, reduce and recycle. Therefore we conducted research on waste management in Islamic boarding schools with students as the subject. The purpose of this research is to increase the awareness of all students in waste management using the reuse, reduce and recycle methods. The method used in this study uses the literature study method.